Bimetallic Nanoparticles Pt–M (M=Cu, Fe, or Ni) Preparation Based on Modified Polyol Method for N2O decomposition activity - Mohd Husin, Mohd Haizal; Kong Yong, Liew; Sim Yee , Chin; Mohd Ridzuan, Nordin (2010)
Pt-M (M = Cu, Fe, or Ni) bimetallic nanoparticles were synthesized by modified polyol method using ethylene glycol (EG) as the solvent and PVP as the stabilisation agent with reduction by using NaBH4 at room temperature. The samples were characterised by transmission electron microscopy (TEM) and analyses confirm that the very fine and monodisperse with narrow size distribution particle with average particle size were 3.1 ± 1.0 nm for Pt-Cu, 4.2 ± 1.3 nm for Pt-Fe and 3.9 ± 1.5 nm for Pt-Ni. XRD results show that there is no peak in the pattern of bimetallic nanoparticles observed unless peak of alumina refer to gamma alumina support. Catalytic decomposition of nitrous oxide over alumina supported Pt based bimetallic testing revealed the enhancing of catalytic activity, when Pt-Cu shows the highest N2O decomposition activity of almost 15% at 200 °C. These activities also become higher with increasing temperature.